Asthma phenotypes in Turkey: a multicenter cross‐sectional study in adult asthmatics; PHENOTURK study. (7th July 2015) - Yildiz, Fusun; Mungan, Dilsad; Gemicioglu, Bilun; Yorgancioglu, Arzu; Dursun, Berna; Oner Erkekol, Ferda; Ogus, Candan; Turktas, Haluk; Bogatekin, Gunhan; Topcu, Fusun; Deveci, Figen; Bayram, Hasan; et al.
Abstract: Background and Aims: To evaluate asthma phenotypes in patients with asthma from different regions of Turkey. Methods: A total of 1400 adult asthmatic patients (mean (SD) age: 44.0 (13.9) years, 75% females) from 14 centers across Turkey were included in this study and a standard questionnaire was applied between the time period of February 2011–January 2012. Results: The disease onset ≥ 40 years of age was higher percentage in obese vs. normal/overweight patients and nonallergic vs. allergic patients ( P  < 0.01). The percentage of patients who had FEV1 values over 80% was higher in allergic than nonallergic and normal/overweight than obese patients ( P  < 0.01). Uncontrolled asthmatics have more severe disease ( P  < 0.01). There were more frequent hospital admissions in nonallergic and uncontrolled asthmatics ( P  < 0.01). Chronic rhino‐sinusitis was the leading comorbid disorder in normal/overweight and allergic asthma, while gastroesophageal reflux disorder was more frequent in nonallergic and uncontrolled asthma ( P  < 0.01). Asthma control rate was the highest (39.0%) in patients from Marmara region among all geographical regions ( P  < 0.05). Conclusion: In conclusion, our findings revealed existence of clinical/trigger related phenotypes based on BMI, allergic status, control level and geographical region with more frequent respiratory dysfunction and/or adverse health outcomes in uncontrolled, obese and nonallergic phenotypes.